To shield or not to shield: shielding may have unintended effects on patient dose in CT - Larjava Heli; Eneh Chibuzor; Niiniviita Hannele (Springer, 2025)
Objectives
The aim of the patient out-of-plane shield is to reduce the patient radiation dose. Its effect on tube current modulation was evaluated with the out-of-plane shield visible in the localizer but absent in the scan range in chest CT with different CT scanners.
Methods
An anthropomorphic phantom was scanned with six different CT scanners from three different vendors. The chest was first scanned without any shielding, and then with the out-of-plane shield within the localizer but outside the imaged volume. All pitch values of each scanner were used. The tube current values with and without the out-of-plane shield were collected and used to evaluate the effect of overscanning and tube current modulation (TCM) on patient radiation dose.
Results
The highest increase in cumulative mA was 217%, when the pitch was 1.531. The tube current value increased already 8.9 cm before the end of the scanned anatomy and the difference between the tube current of the last slices (with and without the out-of-plane shield in the localizer) was 976%.
Conclusion
Applying an out-of-plane shield outside the scanned volume but visible in the localizer images may increase the patient dose considerably if the scanner’s TCM function is based only on localizer images.
Clinical relevance statement
The use of an out-of-plane shield in CT may strongly increase the tube current modulation and thus provide the patient with a higher radiation dose.